Peran Masyarakat dalam Budidaya Rumput Laut (Studi Kasus :Kampung Arar Distrik Mayamuk Kabupaten Sorong) - salmawati, salmawati; Marwey, Nurhafni; Fikri, Awal (Universitas Muhammadiyah Sorong, 2024)
The aim of this research is to describe the role of the community in seaweed cultivation in Arar Village, Sorong Regency. Using a qualitative approach with data collection techniques through interviews, observation and documentation studies. The results of this research show that the people of Arar village play an important role in the seaweed cultivation process, starting from land preparation, planting, care, to harvesting. However, there are still several factors that influence the community's role in seaweed cultivation, such as lack of knowledge and skills, access to markets, and support from the government. The community can determine strategies for developing seaweed cultivation, and as a communication medium for resolving disputes or problems within seaweed cultivation farmer groups in Arar village. By increasing the role of the community in seaweed cultivation, it is hoped that seaweed production can increase and local communities can improve their welfare.